Correlation of quality of life with knowledge and attitude of diabetic elderly - Mariana Campos de Sousa; Flavia Aparecida Dias; Janaína Santos Nascimento; Darlene Mara dos Santos Tavares
Objective.To describe the quality of life (QL), knowledge and attitude of the elderly with diabetes mellitus (DM) and to correlate the QL with the knowledge and the attitude of the elderly. Method. It is a cross-sectional study of household inquiry type and developed with 296 elderly with DM. The used instruments were: World Health Organization Quality of Life Bref (WHOQOL-BREF), World Health Organization Quality of Life Old (WHOQOL-OLD), Diabetes Knowledge Scale Questionnaire (DKN-A) and Diabetes Attitudes Questionnaire (ATT-19). Results. The female were predominant (68.2%), aged from 70 - 79 years old (43.9%), married or living with a partner (41.6%), living with their children (43.2%), with income of one minimum wage (52.4%), had 4 - 7 years of education (32.8%), on diet use and oral hypoglycemic (68.6%) and less than five years diagnosis (29.1%). The greater the knowledge and the attitude the higher QL scores in physical, psychological, social relationships and environment domains; and facets of sensory works, autonomy, and intimacy. Conclusion. Educational activities need to be worked improving the knowledge and attitude of the elderly about the DM.